MOLECULAR CHARACTERIZATION OF RICE (ORYZA SATIVA L) GENOTYPES FOR SALT TOLERANCE USING MICROSATELLITE MARKERS - DAVLA, DEEPTI; N. SASIDHARAN; MACWANA, SNEHA; CHAKRABORTY, SUDESHNA; TRIVEDI, RUCHI; RALLAPALLI, RAVIKIRAN; SHAH, GRISHMA (The Bioscan, 2013)
Salinity stress is the major constraint in rice production. Selection for salinity tolerance genotypes of rice based on phenotypic performance alone is less reliable and will delay in progress in breeding. Recent advent of molecular markers, microsatellites or simple sequence repeats (SSRs) were used to find out salt tolerant rice genotypes. In view of this, the mapping and marker-assisted selection for salt tolerance genes in rice have been conducted. The present study was carried out with the objective of evaluation of genetic diversity among 19 rice genotypes, representing highly tolerant as well as susceptible rice cultivars using SSR markers. Among 39 SSR markers used, 26 SSR marker loci generated polymorphic patterns and a total of 185 alleles were detected. From these 26 SSR markers, 16 SSR markers are located on the Saltol region on chromosome 1 of rice. The number of alleles per locus ranged from 3-11 with a mean of 7.1 alleles per locus. The PIC values for 26 SSR markers varied from 0.50 (RM6737) to 0.89(RM3412) with an average PIC of 6.7. Hence, from the present study, it can be proved that SSR markers can detect high polymorphism and are very useful in studying variation among different genotypes.